The Plight of a Nation without a State: An Analysis of the Struggle of Kurds for an Independent State - Amna Mahmood (IDEA PUBLISHERS, 2020)
Struggle of the Kurds for an independent state can be considered to be one of the most challenging and most underestimated issue in the political analysis of Middle East. Kurd is the fourth largest ethnic group in this region with an estimated populace of 35 to 40 million who are dissipated among four states Turkey, Iraq, Syria and Iran separately. This study intends to examine the origin of Kurds, their political struggle, the factors that compelled Kurdish Regional Government (KRG) of Iraq to conduct referendum for Independence and reaction of all the four countries who share Kurdish population. By adopting exploratory and explanatory approaches and utilizing primary as well secondary data, it has been found that Kurdish struggle and its outcome have been influenced by multiple complex factors which led their conflict to an unresolved state. Our analysis concluded that the states need to realize that suppression of ethnic identities and voices of Kurds might appear to be solution for short time, but not in the long run for promoting peace and regional stability in the Middle-East.